1999
DOI: 10.1074/jbc.274.41.28849
|View full text |Cite
|
Sign up to set email alerts
|

Role of Cytochrome c as a Stimulator of α-Synuclein Aggregation in Lewy Body Disease

Abstract: ␣-Synuclein is a major component of aggregates forming amyloid-like fibrils in diseases with Lewy bodies and other neurodegenerative disorders, yet the mechanism by which ␣-synuclein is intracellularly aggregated during neurodegeneration is poorly understood. Recent studies suggest that oxidative stress reactions might contribute to abnormal aggregation of this molecule. In this context, the main objective of the present study was to determine the potential role of the heme protein cytochrome c in ␣-synuclein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
158
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 220 publications
(165 citation statements)
references
References 33 publications
(32 reference statements)
7
158
0
Order By: Relevance
“…The study involved the selective macroautophagy inhibitor 3Ͳmethyladenine (3ͲMA), which led to a considerable increase of the steady state levels of alphaͲsyn in PC12 cells and in primary cortical and ventral midbrain neurons, suggesting that dysfunction of this degradation process could also contribute to the gradual accumulation of endogenous WT alphaͲsyn in sporadic PD.Furthermore, oxidative stresslinked to mitochondrial dysfunction may also increase misfolded proteins and therefore lead to aggregation of alphaͲsyn and subsequent death of dopaminergic neurons [175]. Thus, alphaͲsyn aggregation itself may also contribute to increased oxidative stress levels, leading to a vicious cycle in the cell [176]. Pesticides like paraquat and maneb were found to lead to proteasomal dysfunction and nitrative/oxidative damage causing an upregulation and subsequent fibrillization of recombinant alphaͲsyn [177,178].…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
See 1 more Smart Citation
“…The study involved the selective macroautophagy inhibitor 3Ͳmethyladenine (3ͲMA), which led to a considerable increase of the steady state levels of alphaͲsyn in PC12 cells and in primary cortical and ventral midbrain neurons, suggesting that dysfunction of this degradation process could also contribute to the gradual accumulation of endogenous WT alphaͲsyn in sporadic PD.Furthermore, oxidative stresslinked to mitochondrial dysfunction may also increase misfolded proteins and therefore lead to aggregation of alphaͲsyn and subsequent death of dopaminergic neurons [175]. Thus, alphaͲsyn aggregation itself may also contribute to increased oxidative stress levels, leading to a vicious cycle in the cell [176]. Pesticides like paraquat and maneb were found to lead to proteasomal dysfunction and nitrative/oxidative damage causing an upregulation and subsequent fibrillization of recombinant alphaͲsyn [177,178].…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…Pesticides like paraquat and maneb were found to lead to proteasomal dysfunction and nitrative/oxidative damage causing an upregulation and subsequent fibrillization of recombinant alphaͲsyn [177,178]. MPTP, a known selective dopaminergic neurotoxin that inhibits mitochondrial complex I activity (as mentionedabove) creates an oxidative stress environment that enhances alphaͲsyn aggregation and consequent death of dopaminergic neurons [176]. Moreover, Dauer and colleagues [179] investigated the toxic effect of MPTP in mice lacking SNCA gene and concluded that these animals were resistant to MPTP, giving support to alphaͲsyn critical role in the pathogenesis of toxinͲinduced dopaminergic neuron death.…”
Section: Alphaǧsynuclein (Snca)mentioning
confidence: 99%
“…Point mutations in R-synuclein that characterize the rare heritable forms of PD have been seen to increase the rate of formation of either fibrils or protofibril intermediates (205 (208), or nitrating reagents (209) induce aggregation/fibrillization of the protein, and human Lewy bodies and other R-synuclein inclusions are positive to antinitrotyrosine antibodies (210). However, oxidation of the four Met residues in R-synuclein to MetO can completely inhibit fibrillization of the peptide if there are no metals around (211).…”
Section: Role Of Oxidative Stress In the Pathogenesis Of Pd And Modelmentioning
confidence: 99%
“…Furthermore, oxidative stress linked to mitochondrial dysfunction may also increase misfolded proteins and therefore lead to aggregation of a-syn and subsequent death of dopaminergic neurons [175]. Thus, a-syn aggregation itself may also contribute to increased oxidative stress levels, leading to a vicious cycle in the cell [176]. Pesticides such as paraquat and maneb were found to lead to proteasomal dysfunction and nitrative/oxidative damage causing an upregulation and subsequent fibrillization of recombinant a-syn [177,178].…”
Section: Oxidative Stress In Familial Pdmentioning
confidence: 99%
“…Pesticides such as paraquat and maneb were found to lead to proteasomal dysfunction and nitrative/oxidative damage causing an upregulation and subsequent fibrillization of recombinant a-syn [177,178]. MPTP, a known selective dopaminergic neurotoxin that inhibits mitochondrial complex I activity (as mentioned above), creates an oxidative stress environment that enhances a-syn aggregation and consequent death of dopaminergic neurons [176]. Moreover, Dauer and colleagues [179] investigated the toxic effect of MPTP in mice lacking the SNCA gene and concluded that these animals were resistant to MPTP, giving support to a critical role for a-syn in the pathogenesis of toxin-induced dopaminergic neuron death.…”
Section: Oxidative Stress In Familial Pdmentioning
confidence: 99%